2019
DOI: 10.1007/s12687-019-00447-2
|View full text |Cite
|
Sign up to set email alerts
|

A large family with CYLD cutaneous syndrome: medical genetics at the community level

Abstract: Germline mutations in the cylindromatosis gene (CYLD) are associated with a rare autosomal dominant disease known as CYLD cutaneous syndrome (CCS). Patients present multiple neoplasms originating from skin appendages. Here, we investigated the main clinical and molecular features of a large family with CCS having lived in a small Brazilian town for 6 generations, making its prevalence significantly high. We observed a predominance of the disease among males and a wide phenotypic variation. A high frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
0
2
Order By: Relevance
“…In a recent study of a South American family with CCS, BCC was reported in 25% of affected patients. 35…”
Section: Malignancy In Ccsmentioning
confidence: 99%
“…In a recent study of a South American family with CCS, BCC was reported in 25% of affected patients. 35…”
Section: Malignancy In Ccsmentioning
confidence: 99%
“…D. Carton de Tournai, 1,2,* I. Vandernoot, 1,3 M. Marangoni, 3 D. Faverly, 4 M. Diaz, 5 A. Casagranda, 1 E. Berlingin, 1 L. Van Maldergem 6,7…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Still, studies have pointed to a strong burden of stigma and prejudice, which adds to the uneven distribution of other social and health vulnerabilities in its territory ( Maia et al, 2015 ; Marçon et al, 2020 ; Brasil, 2021 ). This situation tends to be even more sensitive in geographically isolated areas with a high frequency of albinism, considering that clusters of genetic conditions (especially conditions with a visible, disfiguring phenotype) are places constantly surrounded by myths and beliefs and where there is not always all the necessary health services for comprehensive, timely health care ( Pereira, 2005 ; Arruda et al, 2020 ; Cardoso-dos-Santos et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%